Analisis Hubungan Kadar Hb dan Paritas Ibu Hamil dengan Kejadian Bayi Berat Lahir Rendah (BBLR) di RS Panembahan Senopati Bantul Yogyakarta - Angga Arsesiana (Jurnal Forum Kesehatan, 2019)
Low birth weight babies (LBW) have a greater risk of problems or complications compared to normal birth weight babies (LBW). LBW is a major cause of morbidity and disability. It has a long-term impact on a child's future life and an indicator of the child's health level. This research wants to prove whether there is a corelation between Hb levels of pregnant women and maternal parity with the incidence of LBW in Panembahan Senopati Bantul Hospital in 2017. This research was an observational analytic study with a case control design. Population in this research was mothers who gave birth to LBW babies from January - December 2016 at Panembahan Senopati Hospital Bantul and the control population were all mothers who gave birth to normal weight babies (BBLN) from January - December 2016 at Panembahan Senopati Bantul Hospital. The case sampling used a total sampling technique of 162 samples. While the control sampling using systematic random sampling technique with a calculation of 1701/162 = 10, so the population member that became the control sample were taken at every multiple of 10 and the number of control samples obtained 162 samples. This research was conducted for 1 month by searching secondary data sources obtained from maternal medical records. The dependent variable in this research is the LBW while the independent variable is the maternal Hb level and maternal parity. The analysis used was univariate and bivariate with 95% Chi square test. The results showed there was a corelation between maternal Hb levels with LBW (p-value ꞊ 0,000, OR ꞊ 9,036) and there was a corelation between maternal parity with LBW (p-value ꞊ 0,000, OR ꞊ 9,511). Based on this research it can be concluded that there is a corelation between hemoglobin levels and parity of pregnant women with the incidence of LBW in Panembahan Senopati Hospital Bantul. As for earlier prevention of LBW risk, researcher hope that pregnant women checks their pregnancy routinely.